Penerapan Pelaporan E-kinerja dalam Meningkatkan Kinerja Aparat sipil Negara dengan Model Mediasi Motivasi : - - Suryandari, Rahmah; Radmojo Adji, Askardija; Amir, Ja'far (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of the implementation of e-performance reporting on the performance of the State Civil Apparatus (ASN) in Cimanggis District, with motivation as an intervening variable. This study uses a quantitative approach with a survey method. The population in this study is all ASN in Cimanggis District, while the sample is all employee. Data collection was carried out through a questionnaire distributed to respondents. Data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software. The results of the study show that the implementation of e-performance reporting has a significant positive effect on the performance of ASN. In addition, motivation has been proven to mediate the relationship between the implementation of e-performance reporting and ASN performance. The implication of this study is the importance of implementing effective e-performance reporting to improve ASN performance. The implementation of e-performance reporting can increase the work motivation of ASN so that it has a positive impact on their performance